Correlating fluorescence spectral properties with DOM molecular weight and size distribution in wastewater treatment systems. Issue 12 (5th October 2018) - Xiao, Kang; Shen, Yuexiao; Sun, Jianyu; Liang, Shuai; Fan, Huiju; Tan, Jihua; Wang, Xiaomao; Huang, Xia; Waite, T. David
Abstract : By systematically exploring the EEM spectra, some fluorescence variables are found to correlate with the molecular weight/size (MW) levels of DOM and may usefully reflect the MW in wastewater treatment systems. Abstract : This study explores the potential of a fluorescence excitation–emission matrix (EEM) for indication of DOM molecular weight/size (MW) levels in wastewater treatment systems by systematically investigating the correlations between various fluorescence spectral properties and MW levels. Three types of DOMs from a membrane bioreactor and an oxidation ditch were fractionated into nine grades with apparent MW cut-offs (MWCOs) of 0.7, 0.22 and 0.05 μm and 100, 30, 10, 3, 1 and 0.5 kDa. The EEM overall fluorescence intensity per unit total organic carbon (FI/TOC) and the overall FI per unit UV absorbance (FI/UVA), which represent the gross fluorescence efficiency and apparent quantum yield, respectively, were found to increase significantly as the MWCO decreased from 0.7 μm to 1 kDa. Further elaboration of the excitation (Ex) and emission (Em) spectra revealed that the smaller- and larger-MW fractions tend to occur in the lower-wavelength (Ex < 300 nm, Em < 280 nm) and higher-wavelength (Em > 400 nm) regions, respectively. The EEM spectra in these particular regions produced highly significant relationships between the relative intensity and log-MWCO (from 0.7 μm to 1 kDa) with R 2 > 0.83 at specific Ex/Em positions. The optimal Ex/Em positions for the relationships differed according to the source of the DOM that varies with process types ( e.g. membrane bioreactor vs. oxidation ditch) and process stages ( e.g. sludge mixed liquor vs. membrane effluent). The results of this study provide new insights with regard to the possible use of fluorescence spectroscopy for qualitative or quasi-quantitative indication of DOM MW in wastewater treatment systems.